To Linger on the Edge of Bad Feelings: Thoughts and Advice for Graduate Students on the Unsure Dance of Writing for Publication - Lewkowich, David (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2017)
In this paper, I discuss the process of developing a piece of writing for publication. Written for an intended audience of graduate students in the field of education, I discuss writing for publication as an arrangement for significance, the question of finding a discursive and intellectual home, the selection of an appropriate journal in which to publish, the importance of spaces and rituals of writing, and the conversational dynamics of peer review.